Direct Democracy: Chances and Challenges - Gebhard Kirchgässner (Center for Research in Economics, Management and the Arts (CREMA), 2015)
This paper discusses several problems of direct popular decisions. In the first part, we consid- er problems related to the functioning of direct democracy. As a political system it only makes sense if there exists a continuous process and not if only occasional single questions are brought to a referendum. Then, the relation between direct democracy and the rule of unanim- ity is discussed, a subject of special relevance to the European Union, before we consider the role of quorums. In the second part, some areas are considered in which conflicts might arise. Results of initiatives might be incompatible with individual human rights or might endanger fiscal sustainability, and referenda might impede economic reforms. All these problems, how- ever, do not justify a general re jection of direct popular rights . Thus, we conclude by listing several points that should be observed to safeguard the well-functioning of direct democracy.
Keywords: H11; 330; Direct democracy; referendum; initiative; human rights; economic re- forms; fiscal sustainability